Posicionamiento en el mercado de La Piladora Juanita en el cantón Montalvo - López Bustamante, Yuleidy Natividad (2022)
The present case study entitled market positioning of the Juanita piladora, is carried out with the objective that said establishment implements strategies such as: based on a benefit, based on a characteristic, based on price / quality, based on competition , based on lifestyle among others, that allows them to place themselves in the minds of their real and potential consumers, creating a pleasant perception about the family business, and that it is able to position itself in the market and has key tools that allow it to do face the new changes that arise in the competitive market and, above all, market your product effectively and efficiently.